Impact of an Integrated Pharmacy Transitions of Care Pilot Program in an Urban Hospital. (October 2016) - Christy, Shannon; Sin, Billy; Gim, Suzanna
Purpose: To evaluate the effectiveness of an integrated Pharmacy Transitions of Care (PTC) pilot program on reducing hospital readmissions and improving patient satisfaction. Methods: This prospective observational cohort study compares patients who participated in the PTC program to a control of usual hospital discharged patients during January through April 2014. The PTC program provided discharge medication review, medication counseling, delivery of medications to bedside, clinic scheduling, and follow-up phone calls. The primary outcome measure was 30-day readmissions. Secondary outcomes included emergency department (ED) visits, pharmacist interventions, and patient satisfaction. Results: Seventy patients participated in the PTC program. Compared to the control (n = 725), the study group had decreased 30-day all-cause readmissions (5.7% vs 13.8%, P = .08), 30-day readmissions for the same diagnosis (2.9% vs 8.1%, P = .18), and ED visits (18.6% vs 25%, P = .82). Twenty-five interventions during discharge medication review included discontinuation of unnecessary medications and correction of medication dose or frequency. The majority of patients were satisfied with the medication education provided (94%) and the timely delivery of prescriptions to bedside (96%). Conclusion: There was no significant difference in 30-day readmission rates. However, pharmacists were able to make a positive impact on patient satisfaction and improve understanding of medications during discharge.